Signaling assemblies formed in mast cells activated via Fcepsilon receptor I dimers - Dráberová, Lubica; Lebduska, Pavel; Hálová, Ivana; Tolar, Pavel; Stokrová, Jitka; Tolarová, Helena; Korb, Jan; Dráber, Petr (European journal of immunology, 2004)
Although aggregation of the Fcepsilon receptor I (FcepsilonRI) is necessary for Ag-mediated mast cell triggering, the relationship between the extent of the FcepsilonRI aggregation and subsequent biochemical and topographical events is incompletely understood. In this study, we analyzed the activation events induced by FcepsilonRI dimers, elicited by binding of anti-FcepsilonRI mAb to rat basophilic leukemia cells. We found that, in contrast to extensively aggregated FcepsilonRI, receptor dimers (1) induced a less extensive association of FcepsilonRI with detergent-resistant membranes, (2) delayed the tyrosine phosphorylation and membrane recruitment of several signaling molecules, (3) triggered a slower but more sustained increase in concentration of free cytoplasmic calcium, (4) induced degranulation which was not inhibited at higher concentrations of the cross-linking mAb, and (5) failed to produce clusters of FcepsilonRI, Syk kinase and Grb2 adapter in osmiophilic membranes, as detected by immunogold electron microscopy on membrane sheets. Despite striking differences in the topography of FcepsilonRI dimers and multimers, biochemical differences were less pronounced. The combined data suggest that FcepsilonRI-activated mast cells propagate signals from small signaling domains formed around dimerized/oligomerized FcepsilonRI; formation of large FcepsilonRI aggregates in osmiophilic membranes seems to promote both strong receptor triggering and rapid termination of the signaling responses.
Keywords: mastocyty; Animals; transportní proteiny; Dimerization; Rats; Mast Cells; fosfoproteiny; Enzyme Precursors; Adaptor Proteins, Signal Transducing; Microscopy, Electron; adaptorové proteiny signální transdukční; Tyrosine; Syk Kinase; lidé; Phosphoproteins; dimerizace; Receptors, IgE; intracelulární signální peptidy a proteiny; membránové proteiny; signální transdukce; receptory IgE; elektronová mikroskopie; Signal Transduction; Carrier Proteins; test degranulace bazofilů; fosforylace; aktiny; Actins; Basophil Degranulation Test; Intracellular Signaling Peptides and Proteins; krysa rodu Rattus; Membrane Proteins; tyrosin; kinasa Syk; zvířata; Protein-Tyrosine Kinases; buněčná membrána; prekurzory enzymů; Phosphorylation; tyrosinkinasy; Cell Membrane; Humans